Changes in cropland area in the United States and the role of CRP. (February 2018) - Hendricks, Nathan P.; Er, Emrah
Highlights: Estimates of cropland conversions differ by data source. The Conservation Reserve Program (CRP) is the main driver of changes in cropland. The U.S. government adjusts CRP area in response to changing market conditions. We estimate the change in crop prices under scenarios of changes in CRP area. Abstract: An understanding of the main drivers of land-use change is critical for policy recommendations that aim to meet the challenge of food and environmental security over the coming decades. Here we show that agricultural policy exerts substantial influence on cropland area in the United States through administration of the Conservation Reserve Program (CRP). Looking at changes in the CRP over time and an understanding of how the program is managed suggest that the government adjusts enrolled acres in response to changing market conditions to achieve supply management objectives and due to budgetary reasons. The projected decrease of 12.8 million acres of CRP from 2007 to 2017 is estimated to decrease corn and soybean prices by 8.9% and 5.4%, while a hypothetical return to 2007 CRP acreage is estimated to increase corn and soybean prices by 12.0% and 7.3%.